MONOPOLI (IHTIKAR) DALAM EKONOMI ISLAM DAN IMPLEMENTASINYA PADA REGULASI PERSAINGAN USAHA DI INDONESIA - Niken Baramurti Evieta Enggar Sandy; Umrotul Khasanah (IAIN BONE, 2026)
This study discusses the prohibition of monopolistic practices (ihtikar) from an Islamic economic perspective and its relevance to the implementation of business competition regulations in Indonesia. The purpose of this study is to analyze the compatibility between Islamic economic principles that emphasize justice, balance, and welfare with the provisions of positive law stipulated in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The research method used is qualitative with a library research approach through analysis of various secondary sources such as books, scientific journals, and laws and regulations. The results show that Islam strictly prohibits the practice of ihtikar because it can create economic inequality, reduce public welfare, and violate the principles of justice and welfare. Meanwhile, national regulations through the role of the Business Competition Supervisory Commission (KPPU) have a similar goal, namely preventing market domination and ensuring the creation of healthy competition. However, the implementation of this policy still faces challenges, particularly in the context of the digital economy and weak law enforcement. Thus, the integration of Islamic economic values ​​in business competition regulations is necessary to strengthen the moral and ethical aspects of business, so as to create an economic system that is just, ethical, and oriented towards the welfare of society.